Strategie logistyczne organizacji sieciowych w zapewnianiu dostępności polskich produktów spożywczych na rynku UE - Nowakowska-Grunt, Joanna (Logistic Strategies of Network Organizations, 2005)
The paper presents usage possibility of strategies influencing assurance of accessability of Polish food products in the EU market. Analysis of theoretical basis of accessability problems in logistics theory have been done. The activity of Polish food enterprises in this area have been analysed on this backgroud. The importance of logistics service enterprises has been pointed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 353-362